2018
DOI: 10.1016/j.scs.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Privacy-enhancing aggregation of Internet of Things data via sensors grouping

Abstract: Big data collection practices using Internet of Things (IoT) pervasive technologies are often privacy-intrusive and result in surveillance, profiling, and discriminatory actions over citizens that in turn undermine the participation of citizens to the development of sustainable smart cities. Nevertheless, real-time data analytics and aggregate information from IoT devices open up tremendous opportunities for managing and regulating smart city infrastructures in a more efficient and sustainable way. The privacy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…Furthermore, in most cases they rely on communication protocols that burden the system with extra computational and communication costs [38]. These costs are often prohibitive for devices such as IoT sensors and smartphone wearables in which computational power and storage are limited [3].…”
Section: Multi-party Computationmentioning
confidence: 99%
“…Furthermore, in most cases they rely on communication protocols that burden the system with extra computational and communication costs [38]. These costs are often prohibitive for devices such as IoT sensors and smartphone wearables in which computational power and storage are limited [3].…”
Section: Multi-party Computationmentioning
confidence: 99%
“…The proposed approach is validated using different data formats underlying many services, defined on real mobility data. From a social perspective [18], citizens' grouping can be used as a masking mechanism to lower the information revealed to third-party service providers. Grouping can be performed according to semantic criteria (for instance, the proximity of privacy preferences) or according to physical criteria (e.g., geographic location).…”
Section: Privacy-preserving Data Miningmentioning
confidence: 99%
“…Grouping can be performed according to semantic criteria (for instance, the proximity of privacy preferences) or according to physical criteria (e.g., geographic location). It is shown that when data Average local group error (privacy) and global error (quality of service-aggregation accuracy) in crowdsensing via citizens' grouping [18]. Increasing the group sizes improves privacy, while quality of service remains constant Fig.…”
Section: Privacy-preserving Data Miningmentioning
confidence: 99%
See 2 more Smart Citations